2006
DOI: 10.1128/aem.72.4.2322-2330.2006
|View full text |Cite
|
Sign up to set email alerts
|

rRNA and Poly-β-Hydroxybutyrate Dynamics in Bioreactors Subjected to Feast and Famine Cycles

Abstract: Feast and famine cycles are common in activated sludge wastewater treatment systems, and they select for bacteria that accumulate storage compounds, such as poly-␤-hydroxybutyrate (PHB). Previous studies have shown that variations in influent substrate concentrations force bacteria to accumulate high levels of rRNA compared to the levels in bacteria grown in chemostats. Therefore, it can be hypothesized that bacteria accumulate more rRNA when they are subjected to feast and famine cycles. However, PHB-accumula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…Applying such a sensitive approach as real-time PCR enabled the discovery of considerable changes during the process. Generally, the differences in the RNA level are correlated well with biomass formation rate [29]. Our results (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…Applying such a sensitive approach as real-time PCR enabled the discovery of considerable changes during the process. Generally, the differences in the RNA level are correlated well with biomass formation rate [29]. Our results (Fig.…”
Section: Discussionmentioning
confidence: 61%
“…The presence of these organisms has also been linked to influent compositions. For examples, members of the Gordoniaceae are present at high lipid loading rates (Frigon, Muyzer, van Loosdrecht, & Raskin, ); and members of the Thiotrichaceae are present at high volatile fatty acid concentration and in the presence of sulfides as they are capable of mixotrophic growth (Martins et al., ). Although the links between the influent composition and other environmental factors is not established for all the plant‐specific highly abundant populations, these observations reported here demand further investigations of their role in activated sludge microbial communities.…”
Section: Discussionmentioning
confidence: 99%
“…A survey of activated sludge structured-biomass models indicates the following specific objectives for the developed models: † implementing a fundamental metabolic yield coefficients (the ATP/NADH2 ratio in the oxidative phosphorylation) (Smolders et al 1994;Beun et al 2000;Dicks et al 2001) † predicting transient conditions under the dynamic conditions of activated sludge processes or batch tests (Daigger & Grady 1982b;Smolders et al 1995aSmolders et al , 1995bGrady et al 1996;Beun et al 2000;Lavallé e et al 2002;Vanrolleghem et al 2004;Frigon et al 2006) † predicting microbial activities in different processes (Oerther et al 2001;Frigon et al 2002a;2002b;Stroot et al 2005;Simpson et al 2006) † interfacing with microbial population dynamics results obtained by molecular techniques Gilbride et al 2006) RNA-based models have been developed with all these specific objectives in prospect.…”
Section: Scope and Objectives Of Rrna-structured Biomass Modelsmentioning
confidence: 99%
“…used the rRNA/rDNA ratio to characterize the metabolic activity of Pseudomonas abietaniphila in activated sludge.Using a genetic knockout mutantFrigon et al (2006) observed that the reactor configuration and the ability to produce PHB had an impact on the rRNA level for a pure culture growing in an acetate-fed reactor. Because the intracellular concentration of rRNA varied with process configuration or with the loading as well as with the growth rate, these observations showed that one pseudo steady state can not hold for different process configurations or for different steady states (i.e.…”
mentioning
confidence: 98%